Rondom de Ander in "Na die geliefde land" van Karel Schoeman - Koch, Jerzy (Afrikaanse Letterkundevereniging, 2002)
The aim of this article is to analyse the novel "Na die geliefde land" (1972) by Karel Schoeman, by interpreting the function of 'hulle' ('they') as a category of alienation/distancing. Schoeman presented a future vision of South Africa controlled by an unidentified group of 'them' and showed Afrikaners as a marginalized group, forced to live on farms. A narrow political interpretation dominated in the reception of this book, which was treated as a simulation of the development of the political situation in South Africa. The key argument of this article is that the indeterminate representation of the situation after the revolution is not a weakness of this novel, but a conscious strategy of the author. The article argues that problems concerning political revolution ('Who', 'Why', 'When') are not that relevant in a reading of the novel because "Na die geliefde land" deals mainly with an Afrikaner community’s reactions to a changed situation.
The Other in "Na die geliefde land" (1972) by Karel Schoeman
Keywords: Afrikaans literature; South African literature; Plaasroman; farm novel; Karel Schoeman; utopia; antiutopia; identity